P156 What is telephone access really like for gum clinic patients in the U.K.?. (8th June 2017) - Agathangelou, Gabriela; Khatun, Azra; Yekini, Stephen; Rose, Tom; Foley, Elizabeth; Patel, Raj
Abstract : Introduction: How patients fare when accessing care by telephone at GUM clinics in the UK can be assessed by 'mystery shopping' methods. This study aimed to establish current access levels when contacting clinics by telephone and investigate the potential barriers. Methods: During October – November 2016 all 262 GUM Clinics in the UK were called during clinic opening times on eight occasions, each by male and female researchers posing as patients requesting to be seen as soon possible. Results: Overall 1589/1905 (83.4%) calls were offered an appointment. Of these, 63.7% of 'patients' were invited to attend a walk-in service. Most clinics were consistently contactable, with 72.9% of calls being answered on the first attempt, however 22.9% of clinics were un-contactable at on at least one occasion. Contacting a clinic over four calls can establish the probability of clinic access, with 68.8% of clinics accommodating a minimum of 6/8 callers. The time to speak to a human ranged from 1 second – 39 minutes. The mean length of conversation was 93 seconds, with longer speaking time increasing chance of success. Although male and symptomatic 'patients' spent longer on the phone, females were 14.6% more likely to offered an appointment (p=0.037). Symptomatic scenarios did not have improved access over asymptomatic contacts (p=0.074). Discussion: Access appears to be falling further below the BASHH standard. Various difficulties in establishing contact were identified, including long hold times and the need for multiple call attempts, that may be barriers to patient access.